Oil shale semicoke-based weather-resistant low-cost mulching film and preparation method thereof
Through the acid solution treatment of semicoke of oil shale, nanotitanium dioxide hydrolysis and surface modification technology, combined with polyethylene resin and antioxidants, a low-cost weathering film was prepared, which solved the problem of insufficient weathering performance of semicoke of oil shale. It improves the mechanical and corrosion resistance of the plastic film, realizes resource recycling and cost reduction.
Patent Information
- Application Number
- CN202411290945.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
AI Technical Summary
The weather resistance of oil shale semicokes is insufficient, resulting in a decrease in performance in high temperature or humid environments, affecting the continuity and stability of agricultural production. At the same time, its freight as fuel is high and there is a risk of land pollution.
By pulverizing the oil shale semicoke and treating it in an acid solution, then immersing in a mixed solution of tetrabutyl titanate and ethanol, nanotitanium dioxide is attached, and in a vinyl silane coupling agent and 3,5-bis( The surface modification is carried out in the reaction of trifluoromethyl)styrene and cinnamide, and finally mixed with polyethylene resin and antioxidant, and then extruded and blow-molded to make a low-cost plastic film with weather resistance.
It significantly improves the mechanical properties, weather resistance and corrosion resistance of the mulch film, ensures that good performance can be maintained in high temperature or humid environments, reduces production costs and achieves reasonable recycling of resources.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste recycling, and in particular to an oil shale semi-coke-based weather-resistant low-cost ground film and a preparation method thereof. Background Art
[0002] Oil shale, also known as kerogen, is a solid combustible mineral rich in organic matter and high in ash, with important industrial value. Its main feature is that shale oil can be extracted through low-temperature distillation process. Generally speaking, the oil content of oil shale is greater than 3.5%, and its organic matter content is usually high, mainly composed of sapropelic, humic or mixed materials. These characteristics make oil shale a potential source of energy, and its calorific value generally exceeds 4187 J / g, showing its calorific value advantage as a fuel.
[0003] Oil shale semi-coke is a solid waste produced when shale oil is extracted using low-temperature distillation technology from oil shale. After the shale oil is extracted, the remaining waste residue can be burned, but its calorific value is low and the freight is high, which has certain limitations. Therefore, it cannot be used as a fuel for a long time. Most of the semi-coke is usually directly discarded in nearby waste dumps. The accumulated semi-coke not only occupies a large amount of land and increases the risk of land pollution, but also contains harmful substances such as heavy metals, radioactive elements and some carcinogens. These harmful components will be released into the surrounding environment under the erosion and leakage of rainwater, causing serious soil pollution and damage to the ecological environment. Long-term pollution may also lead to the deterioration of soil structure, causing the land to gradually lose its agricultural production capacity, thereby affecting the agricultural production of surrounding communities and the quality of life of residents.
[0004] The main components of oil shale coke are kaolin and carbon black, which are very suitable for use as additives in polymer materials. If added to polymer materials, it can not only improve, enhance or give new functions to polymer materials, but also reduce the cost of polymer materials. On the other hand, it can expand the application field of oil shale coke and increase the added value of oil shale coke products.
[0005] Chinese patent document CN113943438A discloses a method for preparing an oil shale coke / sodium alginate composite cross-linked film, wherein the oil shale coke / sodium alginate composite film is prepared by adding crushed, calcined and ball-milled oil shale coke into a sodium alginate / glycerol mixed solution for film casting, and the composite film is impregnated in a calcium salt / glycerol mixed solution and an alkaline aqueous solution to obtain an oil shale coke / sodium alginate composite cross-linked film. The prepared composite cross-linked film has excellent mechanical properties, water resistance and acid and alkali resistance, and can be widely used in food packaging, biomedicine or daily chemicals and other fields, but its weather resistance still needs to be improved. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide an oil shale semi-coke-based weather-resistant, low-cost ground membrane and a preparation method thereof. The prepared ground membrane has excellent mechanical properties, weather resistance and corrosion resistance.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme: A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. The oil shale coke is crushed and dispersed in an acid solution, and stirred at 60-80° C. for 2-5 hours, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, immersing the pretreated oil shale semi-coke in a mixed solution of tetrabutyl titanate and ethanol, stirring evenly, then adding an acid solution to hydrolyze the tetrabutyl titanate, after the hydrolysis is completed, removing water and organic solvent, and calcining the product to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing the oil shale semi-coke loaded with nano-titanium dioxide in an ethanol aqueous solution, then adding a vinyl silane coupling agent thereto, stirring for 1-3 hours, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing the double-bond modified oil shale semi-coke composite material in an organic solvent, then adding 3,5-bis(trifluoromethyl)styrene, cinnamamide and benzoyl peroxide thereto, heating and stirring to react, and after the reaction is completed, filtering, washing, drying, crushing and sieving to obtain a composite modified oil shale semi-coke; S5. The composite modified oil shale coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder are placed in a high-speed mixer and mixed evenly, and then sent to a twin-screw extruder for extrusion granulation, and then the granules are blown into film by a blow molding machine to obtain a weather-resistant and low-cost mulch film based on oil shale coke.
[0008] Specifically, in step S2, the mass ratio of pretreated oil shale semi-coke, tetrabutyl titanate, ethanol and acid solution is 4-6:1-2:10-15:5-10, wherein the pH of the acid solution is 4-6.
[0009] Specifically, in step S2, the hydrolysis temperature is 40-60° C., and the hydrolysis time is 6-12 h.
[0010] Specifically, in step S2, the calcination temperature is 800-850° C., and the calcination time is 1-3 hours.
[0011] Specifically, in step S3, the mass ratio of the oil shale semi-coke loaded with nano-titanium dioxide to the vinyl silane coupling agent is 8-12:1-2.
[0012] Specifically, in step S4, the mass ratio of the double-bond modified oil shale semi-coke composite material, 3,5-bis(trifluoromethyl)styrene, cinnamamide and benzoyl peroxide is 10-15:3-5:2-4:0.5-1.
[0013] Specifically, in step S4, the temperature of the heating and stirring reaction is 50-55° C., and the time of the heating and stirring reaction is 4-8 hours.
[0014] Specifically, in step S5, the mass ratio of the composite modified oil shale semi-coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder is 40-50:50-60:10-20:2-4:1-3, and the antioxidant is selected from antioxidant 1010 or antioxidant 168.
[0015] Specifically, in step S5, the thickness of the blown film is 0.05-0.1 mm.
[0016] The present invention also provides an oil shale semi-coke-based weather-resistant low-cost ground film prepared by the above preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses oil shale coke as the main raw material, which not only reduces the production cost, but also realizes the rational recycling of resources, which is in line with the concept of sustainable development; the present invention uses an acid solution to pretreat the oil shale coke, which can effectively remove impurities, increase the specific surface area of the oil shale coke, and improve the efficiency of subsequent reactions.
[0018] (2) The present invention attaches nano-titanium dioxide to the surface and pore structure of pretreated oil shale coke through the hydrolysis reaction of tetrabutyl titanate. Compared with directly mixing oil shale coke and nano-titanium dioxide powder, the problem of uneven mixing is avoided. By introducing nano-titanium dioxide, the weather resistance and mechanical properties of the ground film material are significantly improved.
[0019] (3) The present invention polymerizes and grafts 3,5-bis(trifluoromethyl)styrene and cinnamamide onto the surface of oil shale semi-coke through an addition reaction between double bonds. 3,5-bis(trifluoromethyl)styrene contains fluorine groups and benzene ring structures, which greatly improve the weather resistance of the material; cinnamamide contains amide groups and benzene ring structures, which can enhance the intermolecular interaction of the raw materials and enhance the resistance of the material to chemical substances, thereby enhancing the chemical corrosion resistance of the ground film; 3,5-bis(trifluoromethyl)styrene and cinnamamide work together to enable the prepared ground film to maintain good performance in high temperature or humid environments, thereby ensuring the continuity and stability of agricultural production. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0021] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0022] A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. Preparation of pre-treated oil shale semi-coke The oil shale coke is crushed and dispersed in an acid solution, stirred and treated at 60-80°C for 2-5h, and then centrifuged, washed and dried to obtain the pretreated oil shale coke.
[0023] In this step, the oil shale semi-coke is first crushed and passed through a 400-mesh sieve, and then treated in an acid solution.
[0024] Among them, the acid solution can be selected from sulfuric acid solution, nitric acid solution or hydrochloric acid solution, and the concentration of the acid solution is 0.5-2mol / L, for example, 0.5mol / L, 1.0mol / L, 1.5mol / L, 2mol / L can be selected, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0025] In this step, by pretreating the oil shale coke with an acid solution, impurities can be effectively removed, the specific surface area of the oil shale coke is increased, and the efficiency of subsequent reactions is improved.
[0026] S2. Preparation of oil shale semi-coke loaded with nano-titanium dioxide The pretreated oil shale semi-coke is immersed in a mixed solution of tetrabutyl titanate and ethanol, stirred evenly, and then an acid solution is added to hydrolyze the tetrabutyl titanate. After the hydrolysis is completed, water and organic solvent are removed, and the product is calcined to obtain oil shale semi-coke loaded with nano-titanium dioxide.
[0027] In this step, the mass ratio of the pretreated oil shale semi-coke, tetrabutyl titanate, ethanol and acid solution is 4-6:1-2:10-15:5-10.
[0028] The acid solution can be selected from a sulfuric acid solution, a nitric acid solution or a hydrochloric acid solution, and the pH of the acid solution is 4-6.
[0029] In this step, the hydrolysis temperature is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C, and 60°C can be selected; the hydrolysis time is 6-12h, for example, 6h, 7h, 8h, 9h, 10h, 11h, and 12h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] In this step, the calcination temperature is 800-850°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C, and 850°C can be selected; the calcination time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, and 3h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] In this step, nano-titanium dioxide is attached to the surface and pore structure of the pretreated oil shale coke through the hydrolysis reaction of tetrabutyl titanate. Compared with directly mixing the oil shale coke and nano-titanium dioxide powder, the problem of uneven mixing is avoided. By introducing nano-titanium dioxide, the weather resistance and mechanical properties of the ground film material are significantly improved.
[0032] S3. Preparation of double bond modified oil shale semi-coke composite material The oil shale semi-coke loaded with nano-titanium dioxide is dispersed in an ethanol aqueous solution, and then a vinyl silane coupling agent is added thereto, and the mixture is stirred for 1-3 hours, and then filtered, washed, and dried to obtain a double-bond modified oil shale semi-coke composite material.
[0033] In this step, the mass ratio of oil shale semi-coke loaded with nano-titanium dioxide and vinyl silane coupling agent is 8-12:1-2, for example, 8:1, 8:2, 9:1, 10:1, 10:2, 12:1, 12:2 can be selected, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Wherein, the vinyl silane coupling agent is selected from vinyl trimethoxy silane or vinyl triethoxy silane.
[0035] In this step, a vinyl silane coupling agent is used for surface treatment to introduce carbon-carbon double bonds on the surface, which is beneficial to the subsequent reaction.
[0036] S4. Preparation of composite modified oil shale semi-coke The double-bond modified oil shale semi-coke composite material is dispersed in an organic solvent, and then 3,5-bis(trifluoromethyl)styrene, cinnamamide and benzoyl peroxide are added thereto, heated and stirred for reaction, and after the reaction is completed, filtered, washed, dried, crushed and sieved to obtain the composite modified oil shale semi-coke.
[0037] In this step, the mass ratio of the double-bond modified oil shale semi-coke composite material, 3,5-bis(trifluoromethyl)styrene, cinnamamide and benzoyl peroxide is 10-15:3-5:2-4:0.5-1.
[0038] In this step, the temperature of the heating and stirring reaction is 50-55°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, and 55°C can be selected; the time of the heating and stirring reaction is 4-8h, for example, 4h, 5h, 6h, 7h, and 8h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] In this step, 3,5-bis(trifluoromethyl)styrene and cinnamamide are polymerized and grafted onto the surface of oil shale semi-coke through addition reaction between double bonds. 3,5-bis(trifluoromethyl)styrene contains fluorine groups and benzene ring structures, which greatly improve the weather resistance of the material; cinnamamide contains amide groups and benzene ring structures, which can enhance the intermolecular interaction of the raw materials and enhance the resistance of the material to chemical substances, thereby enhancing the chemical corrosion resistance of the mulch film; 3,5-bis(trifluoromethyl)styrene and cinnamamide work together to ensure that the prepared mulch film can still maintain good performance in high temperature or humid environments, ensuring the continuity and stability of agricultural production.
[0040] S5. Preparation of low-cost weather-resistant mulch film based on oil shale semi-coke The composite modified oil shale coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder are placed in a high-speed mixer and mixed evenly, then sent to a twin-screw extruder for extrusion granulation, and then the granules are blown into film by a blow molding machine to obtain an oil shale coke-based weather-resistant and low-cost ground film.
[0041] In this step, the mass ratio of the composite modified oil shale semi-coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder is 40-50:50-60:10-20:2-4:1-3.
[0042] Wherein, the antioxidant is selected from antioxidant 1010 or antioxidant 168.
[0043] In this step, the mixing temperature in the high-speed mixer is 60-80° C., and the mixing time is 10-20 min.
[0044] The extrusion temperature of the extruder is 150-160°C; the blowing temperature of the blow molding machine is 160-180°C, and the thickness of the blown film is 0.05-0.1mm.
[0045] The present invention is further illustrated below by means of specific embodiments. Oil shale coke was purchased from Shenmu Chuangyou Energy Technology Co., Ltd.; the brand of polyethylene resin: DFDA-7042, was purchased from Dongguan Huaxinfa Plastic Raw Materials Co., Ltd.; the brand of maleic anhydride grafted polyethylene: XR-14L, was purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.; the mesh size of talcum powder was 1200 mesh.
[0046] Example 1 A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. 10 g of oil shale coke was crushed and passed through a 400-mesh sieve, then dispersed in 100 mL of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, 4g of pretreated oil shale semi-coke was immersed in a mixed solution of 1g of tetrabutyl titanate and 10g of ethanol, stirred evenly, and then 5g of sulfuric acid solution with a pH of 4 was added to hydrolyze the tetrabutyl titanate, the hydrolysis temperature was 40°C, the hydrolysis time was 12h, after the hydrolysis was completed, water and organic solvent were removed, and the product was calcined at 800°C for 3h to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing 8 g of oil shale semi-coke loaded with nano-titanium dioxide in 100 mL of 75 wt% ethanol aqueous solution, then adding 1 g of vinyltrimethoxysilane thereto, stirring for 2 h, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 10g of the double-bond modified oil shale semi-coke composite material in 150mL of organic solvent DMF, then adding 3g of 3,5-bis(trifluoromethyl)styrene, 2g of cinnamamide and 0.5g of benzoyl peroxide thereto, heating and stirring at 50°C for 8h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 40 parts of composite modified oil shale coke, 50 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1010 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05mm, thereby obtaining an oil shale coke-based weather-resistant and low-cost ground film.
[0047] Example 2 A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. 10 g of oil shale coke was crushed and passed through a 400-mesh sieve, then dispersed in 100 mL of a 1.0 mol / L sulfuric acid solution, stirred at 80° C. for 2 h, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, immersing 6g of pretreated oil shale semi-coke in a mixed solution of 2g of tetrabutyl titanate and 15g of ethanol, stirring evenly, then adding 10g of sulfuric acid solution with a pH of 5 to hydrolyze the tetrabutyl titanate, the hydrolysis temperature is 60°C, the hydrolysis time is 6h, after the hydrolysis is completed, removing water and organic solvent, and calcining the product at 850°C for 1h to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing 12 g of oil shale semi-coke loaded with nano-titanium dioxide in 100 mL of 75 wt% ethanol aqueous solution, then adding 2 g of vinyltrimethoxysilane thereto, stirring for 3 h, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 15g of the double-bond modified oil shale semi-coke composite material in 150mL of an organic solvent, DMF, and then adding 5g of 3,5-bis(trifluoromethyl)styrene, 4g of cinnamamide and 1g of benzoyl peroxide thereto, heating and stirring the mixture at 55°C for 4h, and after the reaction is completed, filtering, washing, drying and crushing the mixture through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 50 parts of composite modified oil shale coke, 60 parts of polyethylene resin, 20 parts of maleic anhydride grafted polyethylene, 4 parts of antioxidant 1010 and 3 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05 mm, thereby obtaining an oil shale coke-based weather-resistant and low-cost mulch film.
[0048] Example 3 A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. 10 g of oil shale coke was crushed and passed through a 400-mesh sieve, then dispersed in 100 mL of a 1.0 mol / L sulfuric acid solution, stirred at 70° C. for 4 h, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, 5g of pretreated oil shale semi-coke was immersed in a mixed solution of 1.5g of tetrabutyl titanate and 12g of ethanol, stirred evenly, and then 8g of sulfuric acid solution with a pH of 6 was added to hydrolyze the tetrabutyl titanate, the hydrolysis temperature was 50°C, the hydrolysis time was 10h, after the hydrolysis was completed, water and organic solvent were removed, and the product was calcined at 820°C for 2h to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing 10 g of oil shale semi-coke loaded with nano-titanium dioxide in 100 mL of 75 wt% ethanol aqueous solution, then adding 1.5 g of vinyltrimethoxysilane thereto, stirring for 1 h, then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 12g of double-bond modified oil shale semi-coke composite material in 150mL of organic solvent DMF, then adding 4g of 3,5-bis(trifluoromethyl)styrene, 3g of cinnamamide and 0.8g of benzoyl peroxide thereto, heating and stirring at 55°C for 4h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 45 parts of composite modified oil shale coke, 55 parts of polyethylene resin, 18 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 168 and 3 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then use a blow molding machine to blow the pellets into a film at a temperature of 160°C and a film thickness of 0.05 mm, thereby obtaining an oil shale coke-based weather-resistant and low-cost ground film.
[0049] Example 4 A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. 10 g of oil shale coke was crushed and passed through a 400-mesh sieve, then dispersed in 100 mL of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, 5g of pretreated oil shale semi-coke was immersed in a mixed solution of 2g of tetrabutyl titanate and 12g of ethanol, stirred evenly, and then 5g of sulfuric acid solution with a pH of 4 was added to hydrolyze the tetrabutyl titanate, the hydrolysis temperature was 50°C, the hydrolysis time was 10h, after the hydrolysis was completed, water and organic solvent were removed, and the product was calcined at 800°C for 3h to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing 10 g of oil shale semi-coke loaded with nano-titanium dioxide in 100 mL of 75 wt% ethanol aqueous solution, then adding 1.5 g of vinyltriethoxysilane thereto, stirring for 2 h, then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 14g of double-bond modified oil shale semi-coke composite material in 150mL of organic solvent DMF, then adding 4.5g of 3,5-bis(trifluoromethyl)styrene, 2.5g of cinnamamide and 0.6g of benzoyl peroxide thereto, heating and stirring at 55°C for 4h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 48 parts of composite modified oil shale coke, 52 parts of polyethylene resin, 12 parts of maleic anhydride grafted polyethylene, 2.5 parts of antioxidant 168 and 1.5 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05 mm, thereby obtaining an oil shale coke-based weather-resistant and low-cost ground film.
[0050] Comparative Example 1 A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. 10 g of oil shale coke was crushed and passed through a 400-mesh sieve, then dispersed in 100 mL of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, mixing 4 g of pretreated oil shale semi-coke and 0.25 g of nano titanium dioxide (particle size of 60 nm) to obtain an oil shale semi-coke composite material; S3, dispersing 8 g of the oil shale semi-coke composite material in 100 mL of 75 wt% ethanol aqueous solution, then adding 1 g of vinyltrimethoxysilane thereto, stirring for 2 h, then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 10g of the double-bond modified oil shale semi-coke composite material in 150mL of organic solvent DMF, then adding 3g of 3,5-bis(trifluoromethyl)styrene, 2g of cinnamamide and 0.5g of benzoyl peroxide thereto, heating and stirring at 50°C for 8h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 40 parts of composite modified oil shale coke, 50 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1010 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05mm, thereby obtaining an oil shale coke-based weather-resistant and low-cost ground film.
[0051] Compared with Example 1, Comparative Example 1 directly blends the pretreated oil shale semi-coke and nano-titanium dioxide.
[0052] Comparative Example 2 A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. 10 g of oil shale coke was crushed and passed through a 400-mesh sieve, then dispersed in 100 mL of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, 4g of pretreated oil shale semi-coke was immersed in a mixed solution of 1g of tetrabutyl titanate and 10g of ethanol, stirred evenly, and then 5g of sulfuric acid solution with a pH of 4 was added to hydrolyze the tetrabutyl titanate, the hydrolysis temperature was 40°C, the hydrolysis time was 12h, after the hydrolysis was completed, water and organic solvent were removed, and the product was calcined at 800°C for 3h to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing 8 g of oil shale semi-coke loaded with nano-titanium dioxide in 100 mL of 75 wt% ethanol aqueous solution, then adding 1 g of vinyltrimethoxysilane thereto, stirring for 2 h, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 10g of the double-bond modified oil shale semi-coke composite material in 150mL of organic solvent DMF, then adding 3g of 3,5-bis(trifluoromethyl)styrene and 0.5g of benzoyl peroxide thereto, heating and stirring at 50°C for 8h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 40 parts of composite modified oil shale coke, 50 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1010 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05mm, thereby obtaining an oil shale coke-based weather-resistant and low-cost ground film.
[0053] Compared with Example 1, Comparative Example 2 did not add cinnamamide.
[0054] Comparative Example 3 A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke comprises the following steps: S1. 10 g of oil shale coke was crushed and passed through a 400-mesh sieve, then dispersed in 100 mL of a 1.0 mol / L sulfuric acid solution, stirred at 60° C. for 5 h, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, 4g of pretreated oil shale semi-coke was immersed in a mixed solution of 1g of tetrabutyl titanate and 10g of ethanol, stirred evenly, and then 5g of sulfuric acid solution with a pH of 4 was added to hydrolyze the tetrabutyl titanate, the hydrolysis temperature was 40°C, the hydrolysis time was 12h, after the hydrolysis was completed, water and organic solvent were removed, and the product was calcined at 800°C for 3h to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing 8 g of oil shale semi-coke loaded with nano-titanium dioxide in 100 mL of 75 wt% ethanol aqueous solution, then adding 1 g of vinyltrimethoxysilane thereto, stirring for 2 h, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing 10g of the double-bond modified oil shale semi-coke composite material in 150mL of organic solvent DMF, then adding 2g of cinnamamide and 0.5g of benzoyl peroxide thereto, heating and stirring at 50°C for 8h, after the reaction is completed, filtering, washing, drying, and crushing through a 2000-mesh sieve to obtain a composite modified oil shale semi-coke; S5. Place 40 parts of composite modified oil shale coke, 50 parts of polyethylene resin, 10 parts of maleic anhydride grafted polyethylene, 2 parts of antioxidant 1010 and 2 parts of talcum powder in a high-speed mixer, mix at 60°C for 15 minutes, then send them into a twin-screw extruder for extrusion granulation at a temperature of 150°C, and then pass the pellets through a blow molding machine for film blowing at a temperature of 160°C and a film thickness of 0.05mm, thereby obtaining an oil shale coke-based weather-resistant and low-cost ground film.
[0055] Compared with Example 1, Comparative Example 3 does not add 3,5-bis(trifluoromethyl)styrene.
[0056] The performance of the mulch films prepared in Examples 1-4 and Comparative Examples 1-3 was tested as follows: Tensile property test: The longitudinal tensile strength (MPa) and longitudinal elongation at break (%) of the samples were tested according to the test standard GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; Weather resistance test: UV intensity 300W / m 2 , aging temperature 60℃, aging time 168h, test longitudinal tensile strength retention rate (%); Salt water resistance: 5wt% NaCl solution was used for testing, and the soaking period was 50 days. After 50 days, the wrinkles and bubbles on the surface of the film were observed and recorded. Alkali resistance: 30wt% NaOH solution was used for testing, and the soaking time was 100h. After 100h, the wrinkles and bubbles on the surface of the film were observed and recorded; The test results are shown in the following table:
[0057] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A method for preparing a low-cost weather-resistant mulch film based on oil shale semi-coke, characterized in that: The steps include: S1. The oil shale coke is crushed and dispersed in an acid solution, and stirred at 60-80° C. for 2-5 hours, and then centrifuged, washed, and dried to obtain pretreated oil shale coke; S2, immersing the pretreated oil shale semi-coke in a mixed solution of tetrabutyl titanate and ethanol, stirring evenly, then adding an acid solution to hydrolyze the tetrabutyl titanate, after the hydrolysis is completed, removing water and organic solvent, and calcining the product to obtain oil shale semi-coke loaded with nano-titanium dioxide; S3, dispersing the oil shale semi-coke loaded with nano-titanium dioxide in an ethanol aqueous solution, then adding a vinyl silane coupling agent thereto, stirring for 1-3 hours, and then filtering, washing, and drying to obtain a double-bond modified oil shale semi-coke composite material; S4, dispersing the double-bond modified oil shale semi-coke composite material in an organic solvent, then adding 3,5-bis(trifluoromethyl)styrene, cinnamamide and benzoyl peroxide thereto, heating and stirring to react, and after the reaction is completed, filtering, washing, drying, crushing and sieving to obtain a composite modified oil shale semi-coke; S5. The composite modified oil shale coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder are placed in a high-speed mixer and mixed evenly, and then sent to a twin-screw extruder for extrusion granulation, and then the granules are blown into film by a blow molding machine to obtain a weather-resistant and low-cost mulch film based on oil shale coke.
2. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of pretreated oil shale semi-coke, tetrabutyl titanate, ethanol and acid solution is 4-6:1-2:10-15:5-10, wherein the pH of the acid solution is 4-6.
3. The preparation method according to claim 1, characterized in that: In step S2, the hydrolysis temperature is 40-60°C and the hydrolysis time is 6-12h.
4. The preparation method according to claim 1, characterized in that: In step S2, the calcination temperature is 800-850°C, and the calcination time is 1-3h.
5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the oil shale semi-coke loaded with nano-titanium dioxide to the vinyl silane coupling agent is 8-12:1-2.
6. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the double-bond modified oil shale semi-coke composite material, 3,5-bis(trifluoromethyl)styrene, cinnamamide and benzoyl peroxide is 10-15:3-5:2-4:0.5-1.
7. The preparation method according to claim 1, characterized in that: In step S4, the temperature of the heating and stirring reaction is 50-55° C., and the time of the heating and stirring reaction is 4-8 h.
8. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of the composite modified oil shale semi-coke, polyethylene resin, maleic anhydride grafted polyethylene, antioxidant and talcum powder is 40-50:50-60:10-20:2-4:1-3, and the antioxidant is selected from antioxidant 1010 or antioxidant 168.
9. The preparation method according to claim 1, characterized in that: In step S5, the film blowing thickness is 0.05-0.1 mm.
10. The oil shale semi-coke-based weather-resistant low-cost ground film prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
High-density polyethylene composite additive and preparation method thereof
CN119912728A
A high-density polyethylene composite additive and its preparation method
CN119912728B
